A study of perception of international students on quality of Malaysian cars - Cheng, Wei Hin; Md Isa, Filzah; Hoe, Chee Hee (Universiti Utara Malaysia, 2014)
This paper examines how international students in a local public institution perceived the quality of Malaysian-made cars and whether the country of origin is an important factor in determining the purchase decision of a car.A total of 176 full-time registered international students from 12 countries participated as respondents in this research. A purposive sample was used in this research whereby respondents were asked to complete a self administrated questionnaire. The findings supported the literature which indicated that most respondents have a more favorable perception of cars made in the developed countries than cars made in developing countries. The influence of country of origin, also known as the “made in” effect, has been broadly defined as the positive or negative influence that a country’s product of manufacture may have on consumers’ decision processes or subsequent behavior. The result of this research showed that the effect of country of origin is discernible among the respondents.